2020
DOI: 10.2196/17011
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health for Perinatal Depression and Anxiety: Scoping Review

Abstract: Background The perinatal period is a vulnerable time during which depression and anxiety commonly occur. If left untreated or undertreated, there may be significant adverse effects; therefore, access to rapid, effective treatment is essential. Treatments for mild-to-moderate symptoms according to a stepped-care approach involve psychoeducation, peer support, and psychological therapy, all of which have been shown to be efficaciously delivered through digital means. Women experience significant barr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 149 publications
(91 reference statements)
0
63
0
2
Order By: Relevance
“… 38 A gap in mobile phone-based interventions targeting PNA prevention, screening and/or management also seems apparent. 39 Our study did highlight the role and function of support networks and identified key members, including: family, existing friends, peer support group members and/or HCPs. Women in our study tended to gravitate towards members of their social network who could offer empathy based on shared experiences, which echoes the ‘leaning towards peer-support’ described by Walker et al 40 in the context of people experiencing mental health crises.…”
Section: Discussionmentioning
confidence: 94%
“… 38 A gap in mobile phone-based interventions targeting PNA prevention, screening and/or management also seems apparent. 39 Our study did highlight the role and function of support networks and identified key members, including: family, existing friends, peer support group members and/or HCPs. Women in our study tended to gravitate towards members of their social network who could offer empathy based on shared experiences, which echoes the ‘leaning towards peer-support’ described by Walker et al 40 in the context of people experiencing mental health crises.…”
Section: Discussionmentioning
confidence: 94%
“…These five studies have shown that both qualitative perceptions of depressive symptoms and quantitative scores of depressive symptoms improved after interventions using mobile phones. While these early studies are promising, more research needs to be conducted with respect to women living in resource-poor settings, particularly in more rural areas, who typically do not have access to specialty perinatal health services that are more easily accessible in urban centers [ 53 ]. This work is especially important given that at least half of the world’s population cannot access basic health services [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pharmacotherapy limitations have to be regarded in pregnant women. However, there are various forms of psychotherapy, such as cognitive behavioral therapy, mindfulness, interpersonal therapy and the increasing potential of telemedicine, which are completely safe in pregnancy [ 44 ]. Thitipitchayanant conducted a study in Thailand and demonstrated that women with baby blues in whom relaxation methods were used (listening to mp3 recordings three times a day) had much lower levels of allopregnanolone.…”
Section: Discussionmentioning
confidence: 99%